Value for money in UK healthcare public–private partnerships: A fragility perspective. (July 2016) - Santandrea, Martina; Bailey, Stephen; Giorgino, Marco
Healthcare private finance initiatives/public–private partnerships (PFI/PPPs) have favored the provision of health infrastructures and services, but they have been subjected to major criticisms since the value for money assessment of private finance initiatives/public–private partnerships does not consider uncertainties. Using a systematic literature review and content analysis, we identify the sources of uncertainty (i.e. fragilities) associated with UK healthcare private finance initiatives/public–private partnerships. Fragilities are rooted in their financial structure, inadequate ring-fencing of risks and contractual inflexibility. We then discuss such fragilities in light of the evolution of the private finance initiatives/public–private partnership policy in the UK, thus considering private finance 2 and non-profit distributing models. Although much has been done to overcome the shortfalls related to the financial structure of private finance initiatives/public–private partnerships, greater attention has to be paid to the adaptability of the infrastructure and to the risk governance of private finance initiatives/public–private partnerships. Based on these results we then identify new avenues of research considering the potential benefits stemming from diversification of the sources of funding, adaptability of both the contractual requirements and the physical infrastructure and the risk governance.